2011
DOI: 10.1299/jfst.6.976
|View full text |Cite
|
Sign up to set email alerts
|

An Attempt for Suppression of Wing-Tip Vortex Using Plasma Actuators

Abstract: Influence of the flow induced by dielectric barrier discharge (DBD) plasma actuators on the wing-tip vortex is investigated numerically and experimentally. The plasma actuators are installed on the suction side of the NACA0012 airfoil and operated in blowing and suction modes. For the numerical simulation, direct numerical simulation (DNS) based on the finite-difference immersed-boundary method is used. The DNS shows that the circulation parameter, which measures the strength of wing-tip vortex, is reduced by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 27 publications
0
10
0
2
Order By: Relevance
“…Caruana et al (2009) used the plasma jet as a synthetic jet, and Tan et al (2015) showed the heat transfer enhancement of impinging jet by a synthetic jet. By plasma jet (Touchard, 2008, Hasebe et al, 2011, Caruana et al, 2013:…”
Section: Active Jet Flow Controlmentioning
confidence: 99%
“…Caruana et al (2009) used the plasma jet as a synthetic jet, and Tan et al (2015) showed the heat transfer enhancement of impinging jet by a synthetic jet. By plasma jet (Touchard, 2008, Hasebe et al, 2011, Caruana et al, 2013:…”
Section: Active Jet Flow Controlmentioning
confidence: 99%
“…Dielectric Barrier Discharge)を用いた,DBD プラズマアクチュエータがある.これは電磁気現象を利用するので従 来の機械システムによる流体の制御方法よりレスポンスが早いことや軽量であることから注目されている.これ までプラズマアクチュエータを流体制御に用いた研究は,主に航空宇宙分野の翼周りにおいて研究されており, さらには鈍頭物体などの後流制御に応用されている (1)(2)(3)(4)(5)(6) .噴流の研究においては,円形電極を設置し,間欠的にア クチュエータを駆動させることによって,周期的渦輪を発生させる方法…”
Section: 緒 言 近年,様々な流体の制御デバイスが考案されており,動的制御方法の一つとして,誘電体バリヤ放電(Dbdunclassified
“…Many researchers have further investigated the potential of this device. As a result, plasma actuators have found many applications such as flow separation control for airfoils (Post and Corke, 2004), flow control around a circular cylinder (Jukes and Choi, 2009), wind turbine performance enhancement (Greenblat, et al, 2012) and the suppression of vortices (Hasebe, et al, 2011).…”
Section: Introductionmentioning
confidence: 99%